One-pot synthesis of water-soluble polymeric photoinitiator via thioxanthonation and sulfonation process - Temel, Gokhan; Arsu, Nergis (ELSEVIER SCIENCE SA, 2009)
One-pot synthesis of water-soluble side chain thioxanthone polystyrene (PSt-TX-WS) was achieved, and photoinduced polymerization of acrylamide (AAm) in water was performed with PSt-TX-WS in the presence of a tertiary amine. Since the amine is necessary for photopolymerization to occur, it is likely that PSt-TX-WS initiates polymerization of AAm according to the Norrish Type II reaction. The fluorescence quantum yield of PSt-TX-WS was found to be 0.021, and had a phosphorescence lifetime at 77 K of 95 ms. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Free radical polymerization; One-pot synthesis; Polymeric water-soluble photoinitiator; Thioxanthone; IN-CHAIN THIOXANTHONE; COINITIATOR AMINE; FLUORESCENCE; MACROPHOTOINITIATOR; BENZOPHENONE; Chemistry